Synthesis of first strand cDNA from total RNA of Metroxylon sagu LEAF - Baharina Wati, binti Barozah (Universiti Malaysia Sarawak (UNIMAS), 2005)
Well known as a starch producing plant, Metroxylon sagu offer benefits mainly in providing food for people in Malaysia especially in the Sarawak area. Apart from that, it also has a bright potential in the field of food industry. Due to the importance of sago in Malaysia. a molecular study involving cDNA library construction from the leaves was carried out. By designing complementary DNA or cDNA, pattern of protein expression will be known. Furthennore it may assist more comparative study. In this project, the library set up need to accomplish many steps and procedure. Total RNA from leaves was successfully extracted and the concentration was detennined. Besides that, first strand of cDNA was also able to synthesis through the usage of AMY reverse transcriptase enzyme. However, due to time constraint, cDNA library was unable to be set up completely. In view of the fact that it only accomplished halfway, further follow up research should be conducted.